PENGARUH DIMENSI EMOTIONAL INTERACTION TERHADAP PURCHASE INTENTION DAN PERCEIVED USEFULNESS SEBAGAI VARIABEL INTERVENING PADA PRODUK SKINCARE LOKAL DI SOCIAL COMMERCE TIKTOK - Akmalia, Afitrotul; Dewanti, Ratna Listiana (Jurnal EMT KITA, 2024)
This study aims to analyze the effect of emotional interaction dimensions on purchase intention and perceived usefulness as an intervening variable in local skincare products on TikTok social commerce. The sampling technique used in this study was purposive sampling. With a total of 100 respondents (27 men and 73 women), the population of this study consisted of students in the Special Region of Yogyakarta who bought local skincare products on TikTok. Primary data in this study were collected using a questionnaire method via Google Form, which has been tested for validity and reliability. In this study, SmartPls version 4 software was used as an analytical tool to test both the outer model and the inner model. The results showed that familiarity and intimacy have a positive and significant effect on purchase intention, familiarity and intimacy have a positive and significant effect on perceived usefulness, perceived usefulness has a positive and significant effect on purchase intention, and there is an indirect effect of familiarity and intimacy on purchase intention mediated by perceived usefulness.